Pengembangan Keprofesian Berkelanjutan (PKB) Guru: Berlatih Mendesain Asesmen Kompetensi Minimum Kelas Berbantuan Suara untuk Siswa SD - Panca Dewi Purwati; Aldina Eka Andriani; Dewi Nilam Tyas; Muh. Badrus Siroj; Nur Ummi Afifah; Anita Yuniarti Nurjannah; Semiyem Semiyem (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The reading literacy performance of elementary students in the Dwarawati Cluster, Semarang City, showed a decline in 2024, despite the national literacy achievement at the elementary level being categorized as good. This decline is suspected to be caused by the presence of upper-grade students categorized as at risk readers those who are not fluent or unable to read. This situation highlights the need to improve teachers’ competence in developing assessment instruments that accommodate students' needs, particularly in the form of digital literacy assessments with voice assistance (e-text literacy assessments using facilitating reading aloud). This community service program aims to: (1) describe reading risk issues among upper-grade students, (2) analyze the literacy scores from the educational report of the schools in the Dwarawati Cluster, and (3) identify the training needs and steps required to equip teachers in designing voice-assisted digital assessments. The training was implemented through Project-Based Learning and Classwide Peer Tutoring (CWPT) models, involving pre-training sessions, offline and online workshops, demonstrations, mentoring, and product trials with fourth-grade students. The training improved teachers’ knowledge and ability to design digital literacy assessments. The resulting assessment product, known as “AKM Kelas,” was tested with students, including those at risk of reading difficulties, and was proven effective in supporting text comprehension. The novelty of this program lies in the integration of voice into digital literacy assessments, directly designed by teachers through a locally relevant project-based approach. Moreover, the training served as a form of Continuous Professional Development (CPD), enhancing teachers’ professionalism while simultaneously addressing students’ literacy challenges. In conclusion, this training program contributed significantly to both teacher competence and students’ literacy outcomes at the elementary level.